Depletion of thiols leads to redox deregulation, production of 4-hydroxinonenal and sperm senescence: a possible role for GSH regulation in spermatozoa†. Issue 4 (10th November 2018) - Ortega-Ferrusola, Cristina; Martin Muñoz, Patricia; Ortiz-Rodriguez, Jose Manuel; Anel-López, Luis; Balao da Silva, Carolina; Álvarez, Mercedes; de Paz, Paulino; Tapia, Jose Antonio; Anel, Luis; Silva- Rodríguez, Antonio; Aitken, Robert J; Gil, M Cruz; et al.
Abstract: We hypothesized that thiols and particularly glutathione (GSH) are essential for the regulation of stallion sperm functionality. To test this hypothesis, we initially investigated the relationship between sperm function and GSH content, revealing highly significant correlations between GSH, sperm viability, motility, and velocity parameters ( P < 0.001). Furthermore, the deleterious effects of GSH depletion using menadione and 1, 3 dimethoxy 1, 4, naphtoquinone (DMNQ) were able to be prevented by the addition of cysteine, but no other antioxidant. Pre-incubation with cysteine prevented menadione and DMNQ induced damage to sperm membranes after 1 h ( P < 0.001; P < 0.05) and after 3 h of incubation ( P < 0.001, P < 0.05). Pre-incubation with cysteine ameliorated both the menadione- and DMNQ-induced increase in 4-hydroxynonenal ( P < 0.001). As cysteine is a precursor of GSH, we hypothesized that stallion spermatozoa are able to synthesize this tripeptide using exogenous cysteine. To test this hypothesis, we investigated the presence of two enzymes required to synthesize GSH (GSH and GCLC) and using western blotting and immunocytochemistry we detected both enzymes in stallion spermatozoa. The inhibition of GCLC reduced the recovery of GSH by addition of cysteine after depletion, suggesting that stallion spermatozoa may use exogenous cysteine to regulate GSH. Other findings supporting this hypothesis were changes in sperm functionality after BSO treatment and changes in GSH and GSSG validated using HPLC-MS, showing that BSO prevented the increase in GSH in the presence of cysteine, although important stallion to stallion variability occurred and suggested differences in expression of glutamate cysteine ligase. Mean concentration of GSH in stallion spermatozoa was 8.2 ± 2.1 μM/10 9 spermatozoa, well above the nanomolar ranges per billion spermatozoa reported for other mammals. Abstract : Thiols regulate stallion sperm functionality.